Looking into the future ten years later: Big full containerships and their arrival to South American ports - Ricardo J. Sánchez; Daniel E. Perrotti; Alejandra Gomez Paz Fort (Journal of Shipping and Trade (JST), 2021)
Since 2006, when the Emma Maersk broke into the world of shipping, the growth in containership size has remained a continuous trend.For the last 14 years, since 2006, the enlargement of fullcontainerships size has remained a continuous trend since Emma Maersk broke into the world of shipping. This process - that also affected north-south trades - has crucial implications in the shipping business, particularly in the planning of ports and its services and related activities. This paper analyses the global increase in vessel size and forecasts larger vessels' arrival to South American coasts. The paper analyses evidence since 2006 to understand the factors behind the trend for bigger ships (fleets between 18,000 and 24,000 TEU) and introduce a validated methodology for the prediction of the size of container ships. Experts presented a consensus vision in which factors associated with infrastructure, economics, technology, and the environment play a crucial role in driving the trend. Next, the paper presents a methodology for forecasting the size of containerships and applies it to Latin America's trade. The models include two alternative thresholds for the dependent variables (1310 ft LOA and 18,000 TEU of nominal capacity) that are controlled by cascading effect (i.e., the size gap between Latin America and the world's main trade routes), and the economic activity at the destination countries (represented by port activity). Finally, the conclusions highlight the forecast's call to take action on infrastructure planning and investments, analyzing issues such as "economies of scale," concentration, or entry barriers. Overall, the paper warns about the importance of efficient medium-term planning in the port industry to maximize its economic impact.
Keywords: 650; Decoupling; Forecast; Planning; Port; Shipping; ULCS